Gene expression profiling in aggressive digital papillary adenocarcinoma sheds light on the architecture of a rare sweat gland carcinoma. (20th January 2019) - Surowy, H.M.; Giesen, A.K.; Otte, J.; Büttner, R.; Falkenstein, D.; Friedl, H.; Meier, F.; Petzsch, P.; Wachtmeister, T.; Westphal, D.; Wieczorek, D.; Wruck, W.; et al.
Summary: Background: Sweat gland carcinomas are rare cutaneous adnexal malignancies. Aggressive digital papillary adenocarcinoma (ADPA) represents a very rare subentity, thought to arise almost exclusively from the sweat glands of the fingers and toes. The aetiology of sweat gland carcinomas and ADPA is largely unknown. ADPAs are most likely driven by somatic mutations. However, somatic mutation patterns are largely unexplored, creating barriers to the development of effective therapeutic approaches to the treatment of ADPA. Objectives: To investigate the transcriptome profile of ADPA using a sample of eight formalin‐fixed, paraffin‐embedded tissue samples of ADPA and healthy control tissue. Methods: Transcriptome profiling was performed using the Affymetrix PrimeView Human Gene Expression Microarray and findings were validated via reverse transcription of RNA and real‐time quantitative polymerase chain reaction. Results: Transcriptome analyses showed increased tumour expression of 2266 genes, with significant involvement of cell cycle, ribosomal and crucial cancer pathways. Our results point to tumour overexpression of FGFR2 ( P = 0·001). Conclusions: The results indicate the involvement of crucial oncogenic driver pathways, highlighting cell cycle and ribosomal pathways in the aetiology of ADPA. Suggested tumour overexpression of FGFR2 raises the hope that targeting the fibroblast growth factor (FGF)/FGF receptor axis might be a promising treatment for ADPA and probably for the overall group of sweat gland carcinomas. Abstract : What's already known about this topic? Aggressive digital papillary adenocarcinoma (ADPA) is a rare sporadic tumour, arising predominantly from sweat glands of fingers or toes. ADPA is characterized by a local aggressive behaviour, a high recurrence rate and an emerging metastatic potential. ADPA is most probably driven by somatic mutations. However, somatic mutation patterns are largely unexplored. Knowledge of the biology of ADPA is almost completely lacking, creating barriers to the development of effective therapy strategies. What does this study add? We performed gene expression profiling in a well‐defined sample of formalin‐fixed, paraffin‐embedded tissue samples of ADPA. Array‐based transcriptome analyses revealed increased tumour expression of 2266 genes with significant involvement of cell cycle, ribosomal and cancer pathways, and suggests tumour overexpression of FGFR2 . This broadens our understanding of the molecular mechanisms driving these tumours and raises the possibility of potential targeted therapies comprising fibroblast growth factor receptor (FGFR) kinase inhibitors. What is the translational message? Enhanced knowledge of the genetic landscape will facilitate understanding of gene expression as potential predictive biomarkers in ADPA. Serum levels of FGFR2 may be useful biomarkers in patients with ADPA. Understanding of gene expression, correlated with survival and response to therapy, might lead to precision‐medicine approaches. Linked Comment:  Nishida. Br J Dermatol 2019; 180 :987 . Respond to this article